In the University's Ruins, Some Audiovisual Thoughts - Marks, Laura (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2005)
Intellectual production in the university is increasingly in a position to incorporate multiple intelligences, such as visual acuity, bodily intelligence, and the ability to make abductive leaps. However, university knowledge is also increasingly tied to instrumental value; indeed universities are already incorporating the “audiovisual” as intellectual resource and commodity. In the ruins of the historically valued categories reason, culture, and “excellence” on which universities have been built (Bill Readings), creative pedagogy slows down the process whereby experience is translated into signification, signification is translated into communication, and communication is commodified. This argument is built around the experience of a course the author developed titled “Audiovisual Practice.”